2010
DOI: 10.4049/jimmunol.1000681
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoantigens Overcome Human TCRVγ9+ γδ Cell Immunosuppression by TGF-β: Relevance for Cancer Immunotherapy

Abstract: Human γδ cells expressing TCRVγ9 are HLA-unrestricted CTLs with high relevance for cancer immunotherapy. Many tumor cell types produce TGF-β, however, a cytokine strongly immunosuppressive for conventional T CD4, CD8, and NK cells. Whether TGF-β also inhibits TCRVγ9+ lymphocytes was unknown. Because phosphoantigens (PAgs), such as bromohydrin pyrophosphate, selectively activate the antitumor functions of TCRVγ9+ T cells, in this study, we investigated whether TGF-β modulates these functions. We report that TGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…In our report, CD103 + Vd2T cells were less responsive to phosphoantigen, produced lower levels of inflammatory cytokines, and failed to enhance conventional T cell responses. If CD103 expression by Vd2T cells is a consequence of exposure to TGF-b, then this anti-inflammatory mediator may also be responsible for blunting production of IFN-g and TNF-a in the CD103 + subset (52). Impaired TGF-b signaling has already been identified among mucosal abT cells in CD (53); therefore, the altered function of CD103 + Vd2T cells warrants further analysis in the CD intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In our report, CD103 + Vd2T cells were less responsive to phosphoantigen, produced lower levels of inflammatory cytokines, and failed to enhance conventional T cell responses. If CD103 expression by Vd2T cells is a consequence of exposure to TGF-b, then this anti-inflammatory mediator may also be responsible for blunting production of IFN-g and TNF-a in the CD103 + subset (52). Impaired TGF-b signaling has already been identified among mucosal abT cells in CD (53); therefore, the altered function of CD103 + Vd2T cells warrants further analysis in the CD intestine.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 The reverse situation, however, might also occur in these patients, as phosphoantigen-activated cd T cells can overcome Tregs 49 and TGF-b immunosuppressive functions. 50 The above trials demonstrated that Tregs were not significantly induced by these regimens involving only low doses of IL-2, and they did not offer evidence of Treg-based cd T-cell immunosuppression. Therefore, although the utilization of IL-2 in these trials was a concern, its use did not hamper clinical responses.…”
Section: Safety Of CD T-cell Activation In Patientsmentioning
confidence: 93%
“…The in vitro bioactivity of BrHPP (EC 50 ) is 24/nM for TCRVc9Vd2 1 T-cell clones and peripheral blood mononuclear cells, 30 and this drug is produced as Good Manufacture Practice grade for use in humans under the name Phosphostim/IPH1101 (Innate Pharma, France). Zoledronate, a third generation aminobisphosphonate inhibitor of farnesyl pyrophosphate synthase that has been used for osteolysis (Novartis, Switzerland), induces bioaccumulation of endogenous phosphoantigens.…”
Section: Rationale For Harnessing CD Cells In Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Different drugs can be utilized to improve the mechanisms of gd T cell activation: 2,3,8 in particular, synthetic pyrophosphate-containing compounds have been proposed for cancer immunotherapy on the basis of their ability to stimulate gdT cells. [9][10][11][12] Moreover, aminobisphosphonates (N-BPs), in addition to their effect of inhibiting osteoclastic bone resorption, 13 lead to gd T cell activation and proliferation, with a consequent increased number of gd T cells in peripheral blood, displaying antitumor activity [14][15][16][17][18] Indeed, N-BPs, such as zoledronate (Zol), are chemically stable analogs of inorganic pyrophosphate (IPP) that inhibit the mevalonate pathway and upregulate IPP accumulation, promoting antitumor Vg9Vd2 T cells in vitro and in vivo. [15][16][17][18][19][20] For this reason, different N-BPs have been used in anticancer clinical trials.…”
Section: Introductionmentioning
confidence: 99%